Performance of Sunflower Genotypes in Non-Saline and Saline Soils of Southern Bangladesh (Bangladesh Agronomy Journal, 2018)
A research work was conducted with three sunflower genotypes to evaluate their performance in saline and non-saline soil after harvesting of T. Aman rice. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Three genotypes significantly influenced almost all the growth and yield parameters in both non-saline and saline field. Genotype Hysun-33 showed maximum germination percentage in non-saline soil but minimum in saline soil. Whereas, KUSL- 1 performed the best in saline soil but worst in non-saline condition. Hysun-33 produced maximum leaf at flowering in both conditions but minimum leaf by BARI Sunflower-2 in saline soil and by KU-SL-1 in non-saline soil. In both non-saline and saline soils, plant height at flowering, head diameter, total seed head-1 and filled seed head-1 were maximum for the genotype Hysun-33 and that of minimum for the genotype BARI Sunflower-2. Genotype KU-SL-1 showed maximum value for 1000- seed weight followed by Hysun-33 in both saline and non-saline soils. In case of seed yield head-1, Hysun-33 performed best in saline soils but worst in non-saline soil. In non-saline soil, KU-SL-1 produced maximum seed yield head-1. Biomass at harvest, head diameter and number of filled seed head-1 was well correlated with number of seed head and seed yield head-1. Thus genotype Hysun-33 may be considered as best for saline and KU-SL-1 for non-saline soil.Bangladesh Agron. J. 2018, 21(1): 1-7